Handbook of Nanomaterials and Nanocomposites for Energy and Environmental Applications 2020
DOI: 10.1007/978-3-030-11155-7_20-1
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Thermoplastic Starch Biodegradable Nanocomposites

Abstract: The use of polymers capable of being degraded by the action of microorganisms and/or enzymes without causing harmful effects is a strategy in the management of waste and environmental care. Agro-polymers have begun to play a significant role among researchers and industry, since it has been found that these materials are Biodegradable and eco-friendly. Starch is a polymer belonging to the group of polysaccharides, which is produced by almost all plants using it as energy storage. Depending on the botanical ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 78 publications
(98 reference statements)
0
8
0
Order By: Relevance
“…Using the right plasticizer, starch can be heated up to create thermoplastic starch. However, because of their stiffness, brittleness, and poor mechanical and thermal properties, films made entirely of starch are not appropriate for packing purposes [60].…”
Section: Starchmentioning
confidence: 99%
“…Using the right plasticizer, starch can be heated up to create thermoplastic starch. However, because of their stiffness, brittleness, and poor mechanical and thermal properties, films made entirely of starch are not appropriate for packing purposes [60].…”
Section: Starchmentioning
confidence: 99%
“…39 Starch has been widely used for the preparation of thermoplastic materials by combining it with a plasticizing agent. 40,41 Thus, plant residues rich in this polymer have a high potential for processing as conventional thermoplastic polymers.…”
Section: The Plant Cell Wallmentioning
confidence: 99%
“…Regarding the nanocomposites based on starch, polyvinyl alcohol, and layered silicate, several studies were carried out to identify the dependence of the morphology and thermal properties on the type of layered silicate to find the most efficient functional group with which the silicate galleries can be treated [27][28][29][30][31][32][33][34][35][36]. Other studies have focused on the silicate incorporation method into the polymer blends [37], the target filling content [38][39][40][41][42], the dependence of the degree of miscibility on the type of components of the layered silicate mixtures, or the influence of the miscibility degree on the surface defects [43][44][45]. It was observed that the intercalation degree into a starch-PVOH matrix increased if natural multilayered silicate (NaMMT) or NaMMT functionalized with small-volume ammonium ions (Nanocor I 28) were used.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the intercalation degree into a starch-PVOH matrix increased if natural multilayered silicate (NaMMT) or NaMMT functionalized with small-volume ammonium ions (Nanocor I 28) were used. Nanostructured or micro-structured composites can be obtained using this approach [35,36,[38][39][40][41][42]. The incorporation of NaMMT into such matrices during melt compounding without any other treatment [38][39][40][41][42] or by subjecting the layered silicate to a minor mechanical treatment before incorporation into the melts [37,46] was previously studied, but the results were not optimal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation